Analisis Landasan Filosofis, Teologis, Sosiologis Dalam Pelaksanaan Layanan Standar Mutu - Else Meina; Siti Sumartini; Saipul Annur; Asri Karolina (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the integration of philosophical, theological, and sociological foundations in the implementation of quality service standards at SD IT Azizah Palembang and their implications for the quality of learning and educational services. The research employed a qualitative case study approach. Data were collected through interviews, observations, and documentation, and were analyzed thematically. The findings reveal that Islamic values such as amanah (trustworthiness), ihsan (excellence), and itqan (professionalism and perfection in work) are systematically integrated into learning activities, school culture, and administrative services. From a theological perspective, the school’s vision and mission are realized through character building and the strengthening of students’ spiritual values, supported by strategic programs. Sociologically, the implementation of quality services contributes to higher parental satisfaction, increased public trust, and greater community participation. The application of Islamic values in both learning and administrative processes also enhances teacher performance, service efficiency, and institutional professionalism.